2017
DOI: 10.1002/ece3.3586
|View full text |Cite
|
Sign up to set email alerts
|

Comparative population genetic structure of redbelly tilapia (Coptodon zillii (Gervais, 1848)) from three different aquatic habitats in Egypt

Abstract: Recently, tilapia have become increasingly important in aquaculture and fisheries worldwide. They are one of the major protein sources in many African countries and are helping to combat malnutrition. Therefore, maintenance and conservation genetics of wild populations of tilapia are of great significance. In this study, we report the population genetic structure and genetic diversity of the redbelly tilapia (Coptodon zillii) in three different Egyptian aquatic environments: brackish (Lake Idku), marine (Al‐Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Generally speaking, the number of distinct haplotypes, haplotype diversity (Hd) and nucleotide diversity (Pi) represent the standard indices of genetic diversity. In this study, the genetic variability of the mtDNA cytb and D-loop of the four silver carp populations was characterized with high haplotype diversity and low nucleotide diversity, which was often observed in other animals like Baylisascaris schroederi (Zhou et al 2013), Coptodon zillii (Soliman et al 2017) and Hungarian Gidran horse (Nikolett et al 2016). After 6 years of release, both Hd values and Pi values obtained with two markers changed, but the results of the t-test confirmed that the change was not statistically significant.…”
Section: Discussionmentioning
confidence: 73%
“…Generally speaking, the number of distinct haplotypes, haplotype diversity (Hd) and nucleotide diversity (Pi) represent the standard indices of genetic diversity. In this study, the genetic variability of the mtDNA cytb and D-loop of the four silver carp populations was characterized with high haplotype diversity and low nucleotide diversity, which was often observed in other animals like Baylisascaris schroederi (Zhou et al 2013), Coptodon zillii (Soliman et al 2017) and Hungarian Gidran horse (Nikolett et al 2016). After 6 years of release, both Hd values and Pi values obtained with two markers changed, but the results of the t-test confirmed that the change was not statistically significant.…”
Section: Discussionmentioning
confidence: 73%
“…Actually, aquaculture activities in the Tarim river basin are less developed due to the special environment (high salinity and sediment concentration) [ 33 , 34 ], and the natural populations of T. yarkandensis were actually less interfered by agricultural activities. In this context, although anthropogenic factors could affect the genetic structure and differentiation of fish populations [ 35 , 36 ], especially in some economic fish species widely cultured in aquaculture [ 14 , 37 ], we noted that the genetic exchange among most populations mediated by anthropogenic factors was limited in the Tarim River basin. Here, we suggest that the T. yarkandensis populations should be monitored in the long term to avoid significant reductions in abundance due to the genetic characterizations, including the high levels of genetic variation originating from among-population variation and the small effective population size.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the results of NJ tree and PCA, the individuals from TTMH showed differences and had a bigger geographic distance than the others. The genetic differentiation pattern of fish is usually consistent with the water system pattern of distribution [ 32 , 33 ]. It could be explained by the reason that due to the large-scale diversion and interception of water in the middle and upper reaches of the Tarim River, the lower reaches of Tarim River have been cut off [ 28 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 94%